Potential of recycled concrete aggregate pretreated with waste cooking oil residue for hot mix asphalt. (1st June 2019) - Ma, Jianmin; Sun, Daquan; Pang, Qi; Sun, Guoqiang; Hu, Mingjun; Lu, Tong
Abstract: Application of recycled concrete aggregate (RCA) in hot mix asphalt (HMA) is a sustainable alternative to natural aggregate. However, the increased asphalt consumption and decreased mechanical properties induced by the incorporation of RCA limit the extensive substitution of natural aggregates with RCA in HMA. In this paper, an experimental program was carried out to investigate the potential of recycled concrete aggregate pretreated with waste cooking oil residue (WCOR) with the expectation of reducing asphalt consumption and enhancing performance of HMA. The optimum pretreatment process for coarse and fine RCA in terms of content of WCOR, curing time and curing temperature was determined by an orthogonal design method and the grey correlation analysis. Subsequently, a laboratory characterization of HMA incorporating 40% coarse RCA, 40% coarse RCW (RCA pretreated with WCOR), 20% fine RCA and 20% fine RCW was further conducted in terms of optimum asphalt content, resistance to permanent deformation, cracking resistance at low temperature, fatigue performance, moisture sensitivity and dynamic modulus. Finally, scanning electron microscopy (SEM) test and fluorescence microscope (FM) test were performed to provide insight into the mechanism of WCOR-induced performance alteration. The experimental results showed that the pretreatment of RCA with WCOR decreased the optimum asphalt content from 5.4% to 4.5% for HMA incorporating 40% coarse RCA, from 5% to 4.5% for HMA incorporating 20% fine RCA. Moreover, RCA pretreated with WCOR enhanced significantly fatigue life and low temperature performance of HMA, while had a slight adverse effect on moisture sensitivity, permanent deformation resistance and dynamic modulus. Based on the SEM and FM tests, WCOR was observed to penetrate into tiny voids of cement mortar attached on RCA, which contributed to the reduction of optimum asphalt content and enhancement of fatigue life and low temperature performance of HMA.